2021
DOI: 10.2196/29664
|View full text |Cite
|
Sign up to set email alerts
|

Reactance to Social Authority in a Sugar Reduction Informational Video: Web-Based Randomized Controlled Trial of 4013 Participants

Abstract: Background Short and animated story-based (SAS) videos can be an effective strategy for promoting health messages. However, health promotion strategies often motivate the rejection of health messages, a phenomenon known as reactance. In this study, we examine whether the child narrator of a SAS video (perceived as nonthreatening, with low social authority) minimizes reactance to a health message about the consumption of added sugars. Objective This stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…24 Because individuals with diabetes are frequently prompted to change their lifestyle and adhere to medication by their health care practitioners, they may have a higher degree of psychological reactance or nudge fatigue. Prior studies 25,26 have highlighted the difficulties in designing behavioral nudges to avoid arousing . 15 NA reactance in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Because individuals with diabetes are frequently prompted to change their lifestyle and adhere to medication by their health care practitioners, they may have a higher degree of psychological reactance or nudge fatigue. Prior studies 25,26 have highlighted the difficulties in designing behavioral nudges to avoid arousing . 15 NA reactance in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Because individuals with diabetes are frequently prompted to change their lifestyle and adhere to medication by their health care practitioners, they may have a higher degree of psychological reactance or nudge fatigue. Prior studies 25 , 26 have highlighted the difficulties in designing behavioral nudges to avoid arousing reactance in individuals with diabetes. Alternative and more targeted strategies, such as packaging vaccination as part of diabetes care, a multimodel approach with communication tailored specifically for persons with diabetes, or in-home vaccination, may be effective in this group and require further study.…”
Section: Discussionmentioning
confidence: 99%
“…As a type of health communication, health science popularization short videos disseminate health information to the public in an understandable way about healthy diet and lifestyle, vaccination, rational drug use, disease prevention, and other topics. Compared with medical books and newspapers, short videos combine text, images, and sound to make health information more interesting and understandable, which may influence viewers' attitudes and behavior more easily (11)(12)(13)(14). In addition, short videos make it possible to spread health information in just 1 min, which can achieve a large-scale spread among viewers, greatly enhancing the efficiency of health communication.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the public's information adoption behaviors for short videos are closely related to the attributes of the short video. In terms of information sources, it has been demonstrated that the public's perception of health information can be influenced by the source and channel credibility of Internet content (17), and that doctors are perceived to be more qualified, reliable, and professional (12). Regarding information content, highly engaging, clinically relevant stories may be persuasive to patients in changing health attitudes or behaviors (18).…”
Section: Introductionmentioning
confidence: 99%